1 | initial version |

This isn't an answer, I know, but you could make your code a lot simpler:

F = GF(4, 'a')
R.<t> = PolynomialRing(F)
from itertools import product
for x,y,z in in product(F,repeat=3):
h = x*t^2 + y*t + z
for a,b,c,d,e in product(F,repeat=5)
f = t^5 + a*t^4 + b*t^3 + c*t^2 + d*t + e
C = HyperellipticCurve(f,h)

See the documentation for product.

2 | No.2 Revision |

This isn't an answer, I know, but you could make your code a lot simpler:

```
F = GF(4, 'a')
R.<t> = PolynomialRing(F)
from itertools import product
for x,y,z in in product(F,repeat=3):
h =
```~~x~~*t^2 **x*t^2 + *~~y~~t y*t + z
for a,b,c,d,e in product(F,repeat=5)
f = t^5 + ~~a~~*t^4 **a*t^4 + *~~b~~t^3 b*t^3 + ~~c~~*t^2 **c*t^2 + *~~d~~t d*t + e
C = ~~HyperellipticCurve(f,h)~~HyperellipticCurve(f,h)

See the documentation for product.

3 | No.3 Revision |

This isn't an answer, I know, but you could make your code a lot simpler:

```
F = GF(4, 'a')
R.<t> = PolynomialRing(F)
from itertools import product
for x,y,z
```~~in ~~in product(F,repeat=3):
h = x*t^2 + y*t + z
for a,b,c,d,e in product(F,repeat=5)
f = t^5 + a*t^4 + b*t^3 + c*t^2 + d*t + e
C = HyperellipticCurve(f,h)

See the documentation for product.

4 | No.4 Revision |

This isn't an answer, I know, but you could make your code a lot simpler:

```
F = GF(4, 'a')
R.<t> = PolynomialRing(F)
from itertools import product
for x,y,z in product(F,repeat=3):
h = x*t^2 + y*t + z
for a,b,c,d,e in
```~~product(F,repeat=5)
~~product(F,repeat=5):
f = t^5 + a*t^4 + b*t^3 + c*t^2 + d*t + e
C = HyperellipticCurve(f,h)

See the documentation for product.

Copyright Sage, 2010. Some rights reserved under creative commons license. Content on this site is licensed under a Creative Commons Attribution Share Alike 3.0 license.